2019
DOI: 10.1021/acsami.9b09701
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Microfluidic Synthesis of Pd Nanocubes and PdPt Core–Shell Nanoparticles and Their Catalysis of NO2 Reduction

Abstract: Faceted colloidal nanoparticles are currently of immense interest due to their unique electronic, optical, and catalytic properties. However, continuous flow synthesis that enables rapid formation of faceted nanoparticles of single or multi-elemental composition is not trivial. We present a continuous flow synthesis route for the synthesis of uniformly sized Pd nanocubes and PdPt core–shell nanoparticles in a single-phase microfluidic reactor, which enables rapid formation of shaped nanoparticles with a reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…% ≡ 30 ppm), which is among the best optical hydrogen sensors reported. 10 We compounded Teflon AF with colloidal Pd nanoparticles, produced by a scalable continuous flow synthesis process, 27 to create a highly hydrogen-permeable and hydrogen-sensitive nanocomposite material. Finally, we 3D-printed a fully functional sensor cap, which could be placed on a fiber optic connector and facilitated stable hydrogen sensing.…”
Section: Introductionmentioning
confidence: 99%
“…% ≡ 30 ppm), which is among the best optical hydrogen sensors reported. 10 We compounded Teflon AF with colloidal Pd nanoparticles, produced by a scalable continuous flow synthesis process, 27 to create a highly hydrogen-permeable and hydrogen-sensitive nanocomposite material. Finally, we 3D-printed a fully functional sensor cap, which could be placed on a fiber optic connector and facilitated stable hydrogen sensing.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic performance of Au NRs and Au NRs@mSiO 2 was examined by monitoring the CO-oxidation catalytic reaction. In this work, a plug-ow type reactor has been utilized and a 'glass pocket' was integrated inside the externally heated quartz tube as previously reported by our recent work 20 and Fredriksson et al 35,36 This unique reactor design with minimum dead volume enhances the quadrupole mass spectrometer (QMS) ion current for reaction products from our unsupported nanoparticle catalysts. Total gas ow during the reaction was set to 100 mL min À1 through the quartz tube and only 1 mL min À1 portion was directed to pocket reactor.…”
Section: Co-oxidation Reaction On Au Nanorodsmentioning
confidence: 99%
“…For instance, in Bai's work, 17 bare Au nanorods (NRs) were tested for the reduction of nitro compounds, performed at ambient temperature, while Park, et al reported a catalytic test of bare Pt NPs for CO oxidation up to 240 C. 18 Simultaneously, recent applications of unsupported catalysts indicate that the traditional need for a support to enhance the catalytic activity of NPs may be unnecessary when the NPs are optimized to the reaction. 19,20 In a quest to overcome the thermal instability of NPs with well dened shapes, several recent publications have demonstrated that the use of the metal/mesoporous silica core-shell NPs, which can be achieved through several synthetic methods, are of great promise. 21,22 The rst method used to synthesize such structures, also called the surface permeable etching method, begins with the addition of silica monomers to a colloidal solution of pre-synthesized, facetted NPs and obtains porosity through the subsequent mesoporogen of these metalsilica core-shell structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, microfluidic nanoparticle production has been limited only to the synthesis of simple and homogeneous nanoparticles by the molecular mixing of metal ions and reducing agents. [ 26–33 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, microfluidic nanoparticle production has been limited only to the synthesis of simple and homogeneous nanoparticles by the molecular mixing of metal ions and reducing agents. [26][27][28][29][30][31][32][33] Here we propose a facile microfluidic synthesis approach that allows production of a wide variety of metal core-shell nanoparticles by reproducing seed-mediated growth in a microfluidic channel. Figure 1a shows our proposed microfluidic reactor, which is based on the microstructure inversion in a microfluidic channel for multi-scale homogeneous mixing of the reagents and for maintaining a uniform residence time for the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%